2005
DOI: 10.1590/s1984-92302005000200001
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de programas públicos de treinamento : um estudo sobre o impacto no trabalho e na geração de emprego

Abstract: O que explica o sucesso ou o fracasso de programas de treinamento? Este estudo apresenta a avaliação de um programa público de treinamento, a partir do modelo de Hamblin (1978), tendo como variável dependente o impacto do treinamento no trabalho, subdividido em três níveis: comportamento no cargo, na mudança organizacional e no valor final. O delineamento foi de um quase-experimento, com dois grupos experimentais e um grupo de controle, mesclando metodologias quantitativas e qualitativas. A coleta de dados dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
22

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 4 publications
0
4
1
22
Order By: Relevance
“…The present study found no quasi-experiment or field quasiexperiment, neither assessment of interventions or programs, excepting the study by Mourão and Borges-Andrade (2005). The research sample of articles includes scientific articles published in work and organizational psychology national and international magazines within a long period, between 2000 and 2016.…”
Section: Time Series With Multiple Observations: Field Quasi-experimentscontrasting
confidence: 54%
See 1 more Smart Citation
“…The present study found no quasi-experiment or field quasiexperiment, neither assessment of interventions or programs, excepting the study by Mourão and Borges-Andrade (2005). The research sample of articles includes scientific articles published in work and organizational psychology national and international magazines within a long period, between 2000 and 2016.…”
Section: Time Series With Multiple Observations: Field Quasi-experimentscontrasting
confidence: 54%
“…A study that adopted strategy of analysis of alternative explanations to relations between variables in a field quasi-experiment, based on secondary data collected in time series, was that conducted by Mourão and Borges-Andrade (2005), in a successful research that assessed a governmental program in Brazil. Another example of time series analysis is the time-trend study of work leaves for mental and behavioral disorders among nurses, conducted by Falavigna and Carlotto (2013), in which data were obtained from secondary sources (records on absenteeism and diseases that led to work leave).…”
Section: Time Series With Multiple Observations: Field Quasi-experimentsmentioning
confidence: 99%
“…Outros estudos procuram estabelecer relações entre eventos educativos e o processo de MO (p. ex., Ghedine, Testa, & Freitas, 2006;Mourão & Borges-Andrade, 2005). Há constantemente, nesses artigos, uma inferência de aprendizagem organizacional a partir de verificações da aprendizagem dos indivíduos e grupos, conforme mostra a Tabela 5.…”
Section: Dados Sobre Mudanças Organizacionais E Temas Estudadosunclassified
“…Para Bastos (2006), em função de todas estas exigências do mercado de trabalho, é importante promover a discussão sobre a questão da qualificação e formação do trabalhador. Tal discussão, segundo Mourão (2004), vem sendo feita por instituições de ensino superior, escolas técnicas, órgãos de governo, sindicatos e empresas que compõem o sistema produtivo, já que a formação profissional, nos dias atuais, está diretamente ligada a este sistema.…”
Section: Tdande Formação E Qualificação Profissional: Conceitos E Caraunclassified